BONE STUMP FORMATION IN RELATION TO THE MUSCLE TENSION VALUE AT AMPUTATION PLASTIC SURGERY - Shevchuk, V.I.; Bezsmertnyi, Yu.O.; Bezsmertna, H.V.; Shevchuk, S.V. (World of Medicine and Biology, 2018)
Three series of experiments on 41 dogs with amputation in the medium third thigh and muscular plasty with muscle tension 916-962 μH (experimental group), 980-1100 μH and 650-800 μH (control groups). The monitoring lasted 1 and 3 months. In the 1st series of experiments with muscular tension 916-962 μH, already within one month we observed the formation of the bone cortical endplate, the normalization of intraosseous circulation, with the retention of acylindrical bone stump, the structure of cortical diaphysis plate and the content of the bone marrow channel. During the 2nd series of experiments, 17 out of 19 cases showed the stump formation different from the normal diaphysis: asymmetric axes curvature of the amputated bone, conic thinning or bulbous thickening of the end section, reduction in the diameter through periosteal bone formation (osteogenesis). The 3rd series due to insufficient muscular tension showed incomplete bone marrow closure, abrupt microcirculation distortion and reparatory regeneration failure. Сomplete (within biological abilities of the bone tissue) stump formation is possible through muscular tension at amputation plasty 916-962 μH. Such stump tends to show fast healing processes and normalization of intraosseous circulation with the formation within 1 month after the amputation of a bone end plate. Muscle plasty with tension 980-1100 μHin most cases leads to distortions in intraosseous circulation, formation of cone-like or through periosteal regenerates, thickened stumps with axis deflation, resorption and fracture of cortical diaphysis plate. Muscular plasty with muscular tension 650-800 μH prevents from occlusion of the bone marrow cavity leading to distortions in microcirculation and reparatory regeneration, with stump formation entirely different from the normal diaphysis.